Current account dynamics and macroeconomic policy - Makanza, Christine Selina (School of Economics, 2016)
This thesis focuses on the growing current account imbalances in South Africa and how these imbalances are influenced by macroeconomic policy. These issues are dealt with in three related studies. Even though literature argues that fiscal policy may be more capable of attaining current account stability if supported by monetary policy measures, only a few studies actually address the potential of both monetary and fiscal policy to stabilise the current account (Herz and Hohberger, 2013). As a result, our first study establishes stylised facts about the interaction of fiscal policy and the external balance by analysing the fiscal determinants of the current account. The second study establishes stylised facts about the interaction of monetary policy and the external balance by analysing global and domestic monetary determinants of the current account. The third study considers the structure of the economy in South Africa in terms of the share of traded goods vis-à-vis non-traded goods in production and consumption. The study calibrates a Dynamic Stochastic General Equilibrium(DSGE) model that analyses the role of non-traded goods in the determination of the current account and exchange rate. These three studies help to develop an understanding of the current account in South Africa.